Pelatihan Teknik Pengolahan Ikan Dengan Bumbu Rempah Pada Ibu Ibu PKK Gabahan Jombor Sukoharjo - Hanik, Nur Rokhimah; Nugroho, Anwari Adi; Wiharti, Tri; Sihotang, Dini Rosita; Agustina, Melinda (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Residents of Gabahan RT 05 RW 12 Jombor 40% are over 50 years old and 60% are productive couples, school children and toddlers. Most of the population needs healthy and nutritious food, for health and thinking needs. Fish is a food source that contains a lot of protein, fat, vitamins and minerals that are good for health. The objectives of this service are providing counseling on water pollution and pollutants in fish, as well as the function of spices to reduce pollutants and providing training on how to wash fish properly, and cook healthy fish with spices. The methods used are lectures, questions and answers, and practice. The target of this training is to increase understanding of how to process healthy fish by 20%. From the results of the training, it can be concluded that there has been an increase in understanding of fish processing from an average pre-test and post-test score of 34.79 to 84.43, meaning there has been an increase in understanding of 54.36 (119.49%). Healthy fish processing activities with spices and the like still need to be improved, because they are very beneficial for the health of both parents and children.